Escuela Regional de Artes para el Macizo Surcolombiano (2022)
The following monographic document has the purpose of exposing some of the main problems that art and culture currently have in Pitalito Huila, and the great growing demand for artistic training. And theoretically support the importance of the presence of the arts in school. The lack of proper spaces for a municipality like Pitalito, where art is heritage and tradition are more than necessary, at the same time some ref lections will be raised on the subject of the arts, education and its meaning in contemporary society. For this, theoretical information on educational infrastructures, design and applicable construction systems had to be collected. Likewise, an analysis a nd subsequent diagnosis of the reliable experiences and the current situation in Pitalito Huila was carried out, both in the infrastructure dedicated to these activities, as well as in the training and artistic expression to determine a result that allows us to conceive an architectural proposal. . Throughout the investigation, I found innumerable references: theses, articles, methods of educators, philosophers, theorists in the field of art and education. They affirm the importance that art should be given in education for young people. The purpose of our research was to design a regional arts school for Artistic Training and Expression. The conclusions are that a REGIONAL SCHOOL OF ARTS, in Pitalito. It will contribute to training and artistic expression, and practice, as well as culturalproviding spaces for learning artistic exhibition, construction systems applied in architecture, for an unattended population of the Huila region. Keywords: art, culture, school, museum, architecture.